Deep coralligenous outcrops of the Apulian continental shelf: Biodiversity and spatial variability of sediment-regulated assemblages. (1st January 2019) - Piazzi, Luigi; Kaleb, Sara; Ceccherelli, Giulia; Montefalcone, Monica; Falace, Annalisa
Abstract: Structure and spatial variability of coralligenous assemblages of the Apulian continental shelf in the southern Adriatic Sea were investigated. The area consists of small coralligenous outcrops distributed between 30 and 100 m of depth on coarse detritic or muddy bottom. Photographic samples, obtained through a Remotely Operated Vehicle, were analyzed to evaluate the abundance of the main taxa or morphological groups of macroalgae and sessile invertebrates, and the deposited sediment. A multifactorial sampling design was used to compare assemblages at two depth ranges, the shallow outcrops (between 35 and 45 m) and the deep outcrops (between 60 and 70 m), and to determine the main scales of spatial variation. Assemblages were dominated by encrusting and erect sponges, encrusting and filamentous algae, scleractinians, encrusting and erect bryozoans and the Zoantharia Parazoanthus axinellae . Deep assemblages were characterized by lower alpha and beta diversity, and by the decrease or disappearance of sensitive organisms, such as coralline macroalgae, scleractinians and erect bryozoans, and by the dominance of encrusting sponges, P. axinellae and hydrozoans. Sedimentation was higher on deep outcrops and was suggested to be the main driver of differences between shallow and deep assemblages. The peculiar composition of assemblages found in the Apulian continental shelf provides evidence that these outcrops represent an uncommon coralligenous habitat. Highlights: Coralligenous assemblages of the Apulian continental shelf were investigated. Photographic samples, obtained through a Remotely Operated Vehicle, were analyzed. Assemblages of shallow (35–45 m) and deep outcrops (60–70 m) were compared. Sedimentation was higher on deep outcrops. Deep assemblages were characterized by lower alpha and beta diversity.